Benedetto Cotrugli -- The Book of the Art of Trade : With Scholarly Essays from Niall Ferguson, Giovanni Favero, Mario Infelise, Tiziano Zanato and Vera Ribaudo.: With Scholarly Essays from Niall Ferguson, Giovanni Favero, Mario Infelise, Tiziano Zanato and Vera Ribaudo. (2017) - Unknown
No abstract available